Metabolic syndrome and visceral fat thickness in obese adolescents - Lanny C. Gultom; Damayanti R. Sjarif; Evita K. B. Ifran; Partini P. Trihono; Jose R. L. Batubara (Indonesian Pediatric Society, 2007)
Background Metabolic syndrome (MS) is one of the long-termconsequences of obesity which can be found in adolescents. MS iscaused by excessive visceral fat accumulation. The visceral fatthickness (VFT) itself can be measured by using waist circumference(WC) measurement and abdominal ultrasonography. Until now,there are no WC and VFT cut-off points to predict MS in childrenand adolescents. This study used MS criteria based on NationalCholesterol Education Program – Adult Treatment Panel III(NCEP-ATP III) which specifically modified.Objective The objectives of this study are (a) to determine the MSocurrence based on modified NCEP-ATP III in obese adolescents;(b) to measure the VFT by using abdominal ultrasonography in obeseadolescent with MS and obese adolescent without MS.Methods We conducted a cross-sectional study from March toMay 2006. Fifty obese adolescents were recruited from severaljunior and senior high schools in Jakarta.Results Of those 50 obese adolescents, there were 34 subjects withWC>P 80 and 16 subjects with WC <P 80 . Of those 34 subjectswith WC>P 80 , 17 subjects had MS and the others had no MS. Allthe 16 subjects with WC <P 80 did not have MS. The VFT in 17subjects with WC>P 80 who had MS was 5.19 cm (SD 2.07 cm).The VFT in 17 subjects with WC>P 80 who had no MS was 3.94cm (SD 1.62 cm). The VFT in all 16 subjects with WC <P 80 whodid not have MS was 3.54 cm (SD 0.92 cm). All obese adolescentswith MS had WC>P 80 and they also had visceral fat which wasthicker than obese adolescents without MS.Conclusions All obese adolescents with MS have WC>P 80 andthicker visceral fat than obese adolescents without MS; the VFTof obese adolescents without MS, who had WC>P 80 was 3.94cm (SD 1.62 cm), and the VFT of obese adolescents without MS,who had WC <P 80 was 3.54 cm (SD 0.92 cm).